2019
DOI: 10.1063/1.5090045
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the stable atomic trapping sites in Ar lattice

Abstract: Stable atomic trapping sites in the Lennard-Jones face-centered cubic Ar crystals are investigated by means of the global optimization strategy and convex hull concept for thermodynamic stability. Five generic site types are found in full accord with crystallographic intuition: interstitial within tetrahedral and octahedral hollows and substitutions, single, tetra-and hexavacancy. Their identities are established by radial distribution function analysis. Stability regions of these sites are mapped into the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…14 Low activation energies of interstitial oxygen and hydrogen were confirmed by several theoretical works, 5,6,12,35,44,46 whereas preferential occupation of the generic interstitial (IS) and single-substitution (SS) sites by light atoms has been demonstrated by the computational studies of the Lennard-Jones models. 49,50 In our recent theoretical analysis of the oxygen TIM, 35 we found that substitutional atoms can be activated by an indirect mechanism that involves point lattice vacancy defects, in full accord with the textbook concept. 51 We also demonstrated the direct processes of SS to SS migration, similar to hypothetical direct and ring mechanisms considered up until the 1950s for cubic metals and alloys.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…14 Low activation energies of interstitial oxygen and hydrogen were confirmed by several theoretical works, 5,6,12,35,44,46 whereas preferential occupation of the generic interstitial (IS) and single-substitution (SS) sites by light atoms has been demonstrated by the computational studies of the Lennard-Jones models. 49,50 In our recent theoretical analysis of the oxygen TIM, 35 we found that substitutional atoms can be activated by an indirect mechanism that involves point lattice vacancy defects, in full accord with the textbook concept. 51 We also demonstrated the direct processes of SS to SS migration, similar to hypothetical direct and ring mechanisms considered up until the 1950s for cubic metals and alloys.…”
Section: Introductionsupporting
confidence: 62%
“…35 and 57 (see also ref. 49 and 50). In a spherical piece of the perfect fcc RG crystal a smaller spherical domain of the mobile atoms is identified.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible trapping sites of alkali atoms in RG crystals, and their stability, have been recently studied in the literature [53][54][55].…”
Section: Numerical Estimates Of the Atoms-matrix Interaction Energiesmentioning
confidence: 99%
“…Possible trapping sites of alkali atoms in RG crystals, and their stability, have been recently studied in the literature [39][40][41].…”
Section: B Numerical Estimates Of the Host-matrix Interaction Energiesmentioning
confidence: 99%